ANALISIS IMPLEMENTASI PERATURAN DAERAH NOMOR 3 TAHUN 2009 TENTANG RETRIBUSI PELAYANAN DI BIDANG PERHUBUNGAN DARAT (STUDI KASUS RETRIBUSI PARKIR DI KEC. TAMPAN KOTA PEKANBARU - Khairul, Rahmat; Erlinda, Sri; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: the background of this research is there were phenomenal parking attendant not wearing attribute, increasing parking fee’s tariff and not giving parking retribution’s ticket/ coupon to parking service users in TampanSubdistrictPekanbaru City. The formulation of the problem of this research is How the Implementation of province regulation No.3 Year 2009 concerning service-retribution in land transportation (A Casestudy of Parking retribution in TampanSubdistrictPekanbaru City) is. The aim of of this research is to find out the Implementation of province regulation No.3 Year 2009 concerning service-retribution in land transportation (A Case study of Parking retribution in TampanSubdistrictPekanbaru City). This research was conducted in Department of Information and Communication of Pekanbaru City and in TampanSubdistrict. Population of this research was civil servants of Department of Information and Communication of Pekanbaru City, and coordinators of Fee Collector, and Parking attendants and Society of TampanSubdistrict . Purposive sampling technique was used in this research. Data collecting technique used observation, questionnaire, interview, and documentation. Analyzing data used combination method, by data collecting and qualitative analysis. Results of this research show that Implementation of of province regulation No.3 Year 2009 concerning service-retribution in land transportation (A Case study of Parking retribution in TampanSubdistrictPekanbaru City) have good categorized by percentage 34,51%, while enough categorized by percentage 65,49%. Based on a measure rod 51%-100%, according to HusainiUsman in Ali Hamsah, hypothesis is accepted.Keywords: Implementation, provinceregulation, Parking retribution, Parking Attendat